Epidermal Permeability Barrier in the Treatment of Keratosis Pilaris. (24th February 2015) - Kootiratrakarn, Tanawatt; Kampirapap, Kowit; Chunhasewee, Chakkrapong
Abstract : Objectives . To evaluate and compare the efficacy, safety, hydrating properties, and tolerability of 10% lactic acid (LA) and 5% salicylic acid (SA) in the therapy of keratosis pilaris (KP). Material and Method . Patients with KP were randomized for treatment with either 10% LA or 5% SA creams being applied twice daily for 3 months. The patients were clinically assessed at baseline and after 4, 8, and 12 weeks of treatment and 4 weeks after treatment. The functional properties of the stratum corneum (SC) were determined before treatment, 12 weeks, and follow-up phase by high-frequency conductance and transepidermal water loss (TEWL). Results . At the end of the trial, the mean reduction of the lesions from baseline was statistically significant for 10% LA (66%) and 5% SA (52%). During the treatment, higher conductance values were found on both group and this improvement was maintained until the follow up period. No significant differences in transepidermal water loss were observed after treatment. The adverse effects were limited to mild irritation localized on the skin without systemic side effect. Conclusion . The study demonstrated that 10% LA and 5% SA are beneficial to treat KP with the significantly clearance and marked improvement as by instrumental evaluation.